Phenotypic and Genetic Diversity of Local Perilla (Perilla frutescens (L.) Britt.) from Northern Thailand - Pusadee T. (2017)
© 2017, The New York Botanical Garden. Phenotypic and Genetic Diversity of LocalPerilla(Perilla frutescens(L.) Britt.) from Northern Thailand.Perilla frutescens (L.) Britt., an important oil and culinary crop in Asia, is a valuable genetic resource. Despite its nutritional value and historic and cultural importance, research on Perilla has been scarce, particularly as far as its genetic diversity is concerned. The aims of the present study were to assess variability within and between 29 seed samples of P. frutescens collected from farmers in northern Thailand, and evaluation conducted of their genetic, morphological, and agronomic characteristics, and the seed composition, including polyunsaturated fatty acids omega-3, omega-6, and omega-9, and the vitamin E γ-tocopherols. Perilla frutescens (L.) Britt. of northern Thailand is genetically variable, and structured according to origin of collection which was the consequence of local adaptation. The discovery of high levels of polyunsaturated fatty acids, namely α-linolenic acid and γ-tocopherols, in some Perilla samples indicates the potential for utilizing Perilla for its high omega-3 content including as a vitamin E supplement for humans, a prospect that should be taken into account when planning conservation strategies or when Perilla variability is used in breeding programs.